The Local Wisdom Value of Kompang Music in Rupat District, Bengkalis Regency, Riau Province - Fahmi, Nuril; Wadiyo, Wadiyo; Sunarto, Sunarto (Catharsis, 2021)
Kompang music is one of the most famous arts among the Malay community of Bengkalis Regency and its surroundings, including in Rupat District. As a result of cultural products, kompang music has local cultural values (local genius) which become the characteristic or identity of the community. The purpose of this study is to examine the musical aspect of the kompang music performance and the local wisdom value expressed through the kompang music performance. The research method used in this study is a qualitative research method, with a case study approach. The results of this study in terms of musical aspects are divided into two, namely the musical aspect of the kompang song and the musical aspect of the kompang music instruments, while the local wisdom values expressed in the kompang music performance are religious values, leadership values, cooperation values, responsibility values and educational values.